2017
DOI: 10.1080/10428194.2017.1403019
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective, matched paired analysis comparing bendamustine containing BeEAM versus BEAM conditioning regimen: results from a single center experience

Abstract: The combination of carmustine, etoposide, aracytin, and melphalan(BEAM) conditioning regimen in autologous stem-cell transplantation (ASCT) is widely used in patients with relapsed/refractory non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma. It is also an option in patients with very-high risk aggressive NHL in first complete remission (CR). Recently, a phase Ib-II feasibility study using bendamustine replacing carmustine (BCNU) was reported. We report herein a safety and efficacy analysis of bendamustine-EAM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 30 publications
6
29
3
Order By: Relevance
“…It must be mentioned here that we are following a generous hydration policy during conditioning chemotherapy, with 2‐3 L fluid administration daily. In contrast to other comparable studies, no grade II‐IV nephrotoxicity was observed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It must be mentioned here that we are following a generous hydration policy during conditioning chemotherapy, with 2‐3 L fluid administration daily. In contrast to other comparable studies, no grade II‐IV nephrotoxicity was observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Remarkably in this investigation, a significant lower dose of bendamustine was studied (100 mg/m 2 on two consecutive days). 22 Resuming published and our own data, BendaEAM conditioning with following autologous stem cell transplantation leads to longterm remission rates of 55%-65% in HD, MCL, and DLBCL, and of approximately 30%-35% in aggressive T-cell lymphoma and FL.…”
Section: Responsementioning
confidence: 88%
See 1 more Smart Citation
“…20,28 Furthermore, 47% of patients presented with grade III-IV mucositis, which is more frequent than in previous studies on the BEAM regimen. 29,30,31,18 Gastro intestinal toxicity could explain the high rate of septicemia with bacteria from digestive tract but as renal toxicity, it remained manageable and was not associated with increased NRM in our study.…”
Section: Subgroup Analysismentioning
confidence: 56%
“…It has been used as an effective lymphodepleting agent prior to infusion of chimeric antigen receptor (CAR) T-cells [13]. BEN has also been employed as a component of conditioning regimens for autologous hematopoietic cell transplantation (HCT) to treat multiple myeloma, Hodgkin's lymphoma, mantle cell lymphoma, and other non-Hodgkin's lymphomas [10,[14][15][16][17]. More recently, BEN has been implemented in the context of clinical allogeneic HCT and has been studied in murine HCT models, both highlighting its immunomodulatory effects and suggesting favorable immunomodulation resulting in graft-versus-host disease (GvHD) and tumor control.…”
Section: Introductionmentioning
confidence: 99%